The breakup 2.0 : disconnecting over new media - Gershon, Ilana (Ithaca, N.Y. : Cornell University Press, 2010)
""The Breakup 2.0 is intriguing and illuminating. By exploring how college students use Facebook, cell phones, and IM, Gershon deepens our understanding of these media, of young people's lives, and of our evolving definitions of public and private. It's an original and enlightening book."-Deborah Tannen Georgetown University Author of You Just Don't Understand and You Were Always Mom's Favorite!"The Breakup 2.0 is a slick, sharp, highly intelligent encounter with the most important emerging phenomenon of the twenty-first century."-AllucquTre Rosanne Stone ACTLab, University of Texas at Austin" ""The Breakup 2.0 is a fascinating and thoroughly researched anthropological account of how Facebook, instant messaging, and texting reformat the media ecologies within which today's friendships and romantic relationships function and fracture. There is nothing 'virtual,' liana Gershon shows, about these online arenas. Across a wide range of human relations, the form of interaction turns out to be just as crucial as its content."-Stefan Helmreich MIT" "A few generations ago, college students showed their romantic commitments by exchanging special objects: rings, pins, varsity letter jackets. Pins and rings were handy, telling everyone in local communities that you were spoken for, and when you broke up, the absence of a ring let everyone know you were available again. Is being Facebook official really more complicated, or are status updates just a new version of these old tokens?" "Many people are now fascinated by how new media have affected the intricacies of relationships and their dissolution. People often talk about Facebook and Twitter as platforms that have led to a seismic shift in transparency and (over)sharing. What are the new rules for breaking up? These rules are argued over and mocked in venues from the New York Times to lamebook.com, but well-thought-out and informed considerations of the topic are rare." "Ilana Gershon was intrigued by the degree to which her students used new media to communicate important romantic information?such as "it's over." She decided to get to the bottom of the matter by interviewing seventy-two people about how they use Skype, texting, voice mail, instant messaging, Facebook, and cream stationery to end relationships. She opens up the world of romance as it is conducted in a digital milieu, offering insights into the ways in which different media influence behavior, beliefs, and social mores. Above all, this full-fledged ethnography of Facebook and other new tools is about technology and communication, but it also tells the reader a great deal about what college students expect from each other when breaking up?and from their friends who are the spectators or witnesses to the ebb and flow of their relationships. The Breakup 2.0 is accessible and riveting."--BOOK JACKET.
Fifty ways to leave your lover : media ideologies and idioms of practice -- E-mail my heart : the structure of technology and heartache -- Remediation and heartache -- How do you know? -- Breaking up in public.
Includes bibliographical references and index.
Keywords: Digital media -- Social aspects; Digital media -- Psychological aspects; Separation (Psychology) -- Technological innovations -- Social aspects; Rejection (Psychology) -- Technological innovations -- Social aspects; Interpersonal communication -- Technological innovations -- Social aspects; Online etiquette